Uncinate process first: a novel approach for pancreatic head resection - Hackert, Thilo; Werner, Jens; Weitz, Jürgen; Schmidt, Jan; Büchler, Markus W. (Langenbeck's archives of surgery, 2010)
Partial pancreatico-duodenectomy is the standard treatment for malignancies of the pancreatic head. We describe a technical modification with a retrograde dissection of the pancreatic head as a novel surgical approach.
Gesehen am 12.06.2023